Role of aspiration cytology in splenic lesions - Garg, Shweta; Malik, Nisha; Sharma, Veena (International Journal of Research in Medical Sciences, 2016)
Background: Splenic fine needle aspiration cytology (FNAC) as a diagnostic procedure has been used since beginning of last century and was first reported in 1916. The objective of the study was to evaluate the diagnostic role of aspiration cytology in splenic lesions. Methods: In our retrospective study Fine needle aspiration cytology (FNAC) of spleen was done in a total 34 cases, out of which 28 cases were aspirated under ultrasonological guidance and 6 cases were aspirated blindly. There were 23 male and 11 female patients and the age range of the patients was from 2 to 69 years with 8 patients from paediatric group. Before commencing the procedure all the necessary precautions and investigations including coagulation profile were done. Results: Out of 34 FNAC cases, 5 were bloody aspirate while 2 cases showed normal splenic aspirate. In 27 cases definite diagnostic opinion was possible. Amongst non-neoplastic group maximum patients (8 cases) were showing features of extra medullary hematopoeisis followed by 4 cases of tuberculosis, then 3 cases each of kala azar and storage disorder and 2 cases showed granulomas. In the neoplastic group, we had 2 cases of non-Hodgkins lymphoma, one case of Hodgkin lympoma with 2 cases of hairy cell leukemia and one case of histiocytosis. No major difference in the cellularity noticed when the aspiration done blindly or under ultrasound guidance No procedural complications were seen in our study. Conclusion: Hence when done with full precautions FNAC spleen is a safe, cheap, rapid and highly diagnostic procedure as a primary investigation.